Mood states and self-rated health of Brazilian jiu-jitsu fighters in competition (Revista de Artes Marciales Asiáticas, 2019)
Brazilian Jiu-Jitsu (BJJ) athletes are subjected to a large and intensive training load that may cause injuries. These injuries can be detrimental to the physical and mental health of these athletes. In this regard, the aim of this study was to compare the self-reported health and mood states of BJJ athletes. Twenty-three BJJ athletes participated in the study. A questionnaire was used for general characterization of the athletes, which included the self-rated health question, and the Brunel Mood Scale – BRUMS were used. The mood profile was similar to the Iceberg profile. Athletes with regular health had lower vigor than athletes with excellent vigor. Lower vigor in athletes who reported regular health may be related to concern about injury. Specific strength training and careful execution of the technique should be emphasized in training.